2018
DOI: 10.1186/s13052-017-0440-2
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to allergy in adoptive children: a cross-sectional study at “Bambino Gesù Children’s Hospital”

Abstract: BackgroundPrevalence of allergy has steeply increased during the past few decades, particularly in high-income countries. The development of atopy could present different characteristics in internationally adopted children with regard to incidence, specific patterns of allergies and timing of occurrence. We aimed to investigate the occurrence of allergic diseases among adopted children in Italy.MethodsWe collected demographic information, preadoption immunization data, infectious diseases screening results, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The primary search identified 749 records. The titles and abstracts were screened, 41 full-text papers were assessed for eligibility, and 19 studies fulfilled our inclusion criteria (Table 1) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These studies were conducted between 1988 and 2016 and covered 7663 children aged between 1.1 and 5.7 years, who were adopted from Asia, Eastern Europe, Africa and South and Central America.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary search identified 749 records. The titles and abstracts were screened, 41 full-text papers were assessed for eligibility, and 19 studies fulfilled our inclusion criteria (Table 1) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These studies were conducted between 1988 and 2016 and covered 7663 children aged between 1.1 and 5.7 years, who were adopted from Asia, Eastern Europe, Africa and South and Central America.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of adopted children with protective antibody titres for diphtheria, tetanus, pertussis, hepatitis B, measles, mumps, rubella and varicella varied in the published studies that we examined. Tetanus protective antibody levels were observed in 35–95% of adopted children, and similar data were reported for diphtheria . A higher percentage of adoptees had protective antibody levels for polio and measles, varying from 57 to 90% and 36 to 90%, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Research from Italy showed a high prevalence of atopic disorders in immigrants from extra-European countries, with a similar spectrum of sensitization to the Italian population, but possibly greater severity and among children more prevalent allergic rhinitis [ 45 48 ]. A further study in adoptive children examined soon after arrival in their new home country showed sensitizations (based on serum IgE analyses against food and inhalant allergens in 30 and 34%, respectively [ 49 ].Overall our results on sensitizations are in line with those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on migrating families revealed a big discrepancy in the prevalence of food allergy if there is a mismatch between the pre-conception, antenatal and postnatal environment. For example, if the mother conceives and gives birth in a new country, the baby has a higher risk of food allergy and AD compared to babies who were born in the country of maternal origin ( 136 , 137 ). This amply illustrates that environmental factors rather than genetics had contributed to the increasing prevalence of food allergy.…”
Section: Unmet Need and Future Researchmentioning
confidence: 99%